Nextcloud 2 Terabyte LAN Network-Based Server By Using the Ubuntu LTS 16.04 - Richard Ronaldo Marbun; Iskandar Fitri; Agus Iskandar (Jurnal Teknik Informatika C.I.T Medicom, 2020)
Technology Developmenare currently experiencing significant changes from age to age. And the need to store a data is changed, and each user's data storage require large storage capacity. At reasonable costs, as well as more structured management systematization. So on this research platform in use that is nextcloud, Where the private cloud concept designer can only add users and storage. And in accessing nextcloud based Local Area Network (LAN), the designer to take advantage of to change the IP DNS server into a domain that the user or more designers nextcloud easy access to the internet.Nextcloud